Building an Innovation Ecosystem to Support the Commercialization of Intellectual Property at Vietnam National University, Hanoi - Long, Luu Hoang (VNU Journal of Science: Policy and Management Studies, 2025)
On January 9, 2025, the Government issued Resolution No. 03/NQ-CP on the Action Program for implementing Resolution No. 57-NQ/TW of the Politburo, which mentions the commercialization of research outcomes and the effective exploitation of intellectual property assets (IPAs) at higher education institutions. A survey conducted across 11 universities and 3 research institutes under Vietnam National University, Hanoi (VNU) reveals that while basic and applied research activities have achieved encouraging results in recent years, the commercialization of IPAs—derived from applied research—has not yet been commensurate with their potential. Based on the survey findings, this paper proposes the development of an “innovation ecosystem” to support the commercialization of IPAs in higher education institutions in general and at VNU in particular. The proposed model aims to promote scientific research, enhance the commercial exploitation of university intellectual assets, and contribute to the knowledge-based economy, thereby advancing the implementation of Resolution No. 57-NQ/TW dated December 22, 2024, of the Politburo on breakthroughs in science, technology, innovation, and national digital transformation. Keywords: Commercialization of Intellectual Property; Innovation Ecosystem; Innovation Startup Incubator.